Critical considerations about the theories of Raewyn Connell and Judith Butler for the study of masculinities - Bagiotto Botton, Fernando (Revista Crítica Histórica, 2022)
We will carry out an unpretentious critical balance of some theoretical possibilities on the issue of masculinity from a dialogue established by us between the sociologist Raewyn Connell and the philosopher Judith Butler. We will start our text with some doubts about the way we study masculinities contemporaneously, in a set of reflections of epistemological foundation that, in our view, have few answers, but which cross the problems raised by the debated researchers. We will move on to a critique of Connell’s theory of hegemonic masculinities and then present some possibilities for analysis that can be appropriated from Butler’s queer theory. Therefore, we will try to trace some points of confluence between the most recent readings carried out by Connell and his epistemologically tense but politically parallel relationship with Butler’s studies.